Primary hyperparathyroidism and neuropsychiatric symptoms. Issue 3 (22nd August 2018) - Narayana, Usha; Ashton, Katy; Rivers, Emma; Nirodi, Pratibha
Abstract : The psychiatric and metabolic symptoms associated with hyperparathyroidism are complex and the correlation between symptom severity and degree of hypercalcaemia is poor. Here, the authors explore such a case of hypercalcaemia and primary hyperparathyroidism which required psychotropic medication and a plan for surgical treatment in the longer term.